2006
DOI: 10.1073/pnas.0603533103
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 deficiency causes Sonic hedgehog-independent holoprosencephaly

Abstract: The telencephalic neuroepithelium (NE) of mammalian brain has an apical-basal polarity that is marked by the positioning of neural progenitors and adherens junctions on the apical͞ventricular surface and the ascending of radial glia͞progenitor fibers toward the pial͞basal surface. The signaling pathway that establishes this apical-basal polarity of NE is not completely understood, but the Rho-family GTPase Cdc42 may play a critical role because it controls cadherin-based intercellular junctions and cell polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 31 publications
(43 reference statements)
9
115
1
1
Order By: Relevance
“…Although Cdc42 deletions in previous reports also showed their essential roles in adherens junctions in the nervous system (14,15), there are also significant differences in the phenotypes of RhoA and Cdc42 deletions, even when the same Cre driver (i.e., Foxg1-Cre mice) was used. In Foxg1-Cdc42 null embryos, the disappearance of apical cadherin-catenin proteins started as early as E9.5-E10.5, causing holoprosencephaly due to failure to expand the telencephalon (15). In contrast, RhoA deletion by Foxg1-Cre or Wnt1-Cre drivers caused a gradual disruption of apical cadherin-catenin protein localization between E11.5 and E14.5.…”
Section: Differential Roles Of Rhoa and Cdc42 In Adherens Junctions Omentioning
confidence: 92%
See 1 more Smart Citation
“…Although Cdc42 deletions in previous reports also showed their essential roles in adherens junctions in the nervous system (14,15), there are also significant differences in the phenotypes of RhoA and Cdc42 deletions, even when the same Cre driver (i.e., Foxg1-Cre mice) was used. In Foxg1-Cdc42 null embryos, the disappearance of apical cadherin-catenin proteins started as early as E9.5-E10.5, causing holoprosencephaly due to failure to expand the telencephalon (15). In contrast, RhoA deletion by Foxg1-Cre or Wnt1-Cre drivers caused a gradual disruption of apical cadherin-catenin protein localization between E11.5 and E14.5.…”
Section: Differential Roles Of Rhoa and Cdc42 In Adherens Junctions Omentioning
confidence: 92%
“…The recent development of a conditional gene-targeting strategy has provided many new insights into the physiological functions of small Rho GTPases (13). For example, although Cdc42 and Rac1 are both implicated in epithelial apical junctions, conditional gene deletion in the telencephalon revealed that Cdc42, but not Rac1, is indispensable for the formation of apical adherens junctions in the developing brain (14)(15)(16). These findings underlie the importance of using conditional gene deletion to ascertain the biological functions of small Rho GTPases.…”
Section: Cns Development | Cell Adhesionmentioning
confidence: 97%
“…Whether Cdc42 plays a role in HSC differentiation into various blood cell lineages will be an important question to address in future studies. Another aspect of this study is the implication that Cdc42 function in HSCs is unique, as Cdc42 is known for neuro-stem/ progenitor cell polarity establishment and for skin stem/ progenitor differentiation into the follicle lineage (28)(29)(30) and is required for supporting cell cycle progression through the G 1 /S phase, rather than maintaining cell cycle quiescence, in mouse embryonic fibroblasts (14,31). The findings further suggest an avenue for manipulating the HSC cell cycle status as well as the HSC-niche interaction in future therapeutic applications.…”
Section: Resultsmentioning
confidence: 99%
“…The results of reduction in cellular polarity in the VZ are highly variable even with the same gene involved. For example, conditional knockout of cdc42 was carried out using different Cre drivers, in both cases reduced ventricular cell polarity was observed, followed by changes in cell fate (Chen et al 2006) or holoprosencephaly, a fusion of the two hemispheres (Chae et al 2004).…”
Section: Cell Polarity and Interkinetic Nuclear Movementsmentioning
confidence: 99%